Kalabu (Kalamansi and Purple Sweet Potato) Snack Bar Innovation as an Alternative Snack for Diabetes - Ismiati; Patroni, Rini; Andeka Marleni, Wisuda; Febryanti, Ade (CV Media Inti Teknologi, 2024)
Diabetes mellitus (DM) is a metabolic health disorder characterized by high blood sugar levels (hyperglycemia). Factors that can cause diabetes are heredity and an unhealthy lifestyle. The innovation of healthy snack bar 'Kalabu' aims to support the Healthy Living Community Movement (GERMAS). Snack bar